NAVIGATING THE DIGITAL FRONTIER: UNRAVELING THE DIMENSIONS OF DIGITAL FINANCIAL LITERACY - Idarni Harefa; Tri Hartati Sukartini Hulu, Nanny Artatina Bu’ulolo (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The aim of this study is investigate specific dimensions of digital financial literacy (awareness, skills, knowledge, behavior) in diverse contexts, including rural areas and various demographic groups. Identify and understand the determinants that influence digital financial literacy, providing insights for targeted interventions and educational programs. The paper offers a focused investigation into a specific aspect of essential for anyone seeking a comprehensive understanding of digital financial literacy, its determinants, consequences, and the roadmap for future research and action in this critical and evolving field. Looking ahead, the outlined future agendas provide a roadmap for adapting to technological shifts, fostering financial innovation, and addressing regulatory challenges. Tailored programs, international collaboration, and a focus on psychological aspects aim to create more inclusive strategies. Through these efforts, we anticipate not only advancing our collective understanding of digital financial literacy but also making tangible contributions to promoting financial well-being in our continually evolving digital era.